If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 7 + b Solving 3 = 7 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 3 + -1b = 7 + b + -1b Combine like terms: b + -1b = 0 3 + -1b = 7 + 0 3 + -1b = 7 Add '-3' to each side of the equation. 3 + -3 + -1b = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -1b = 7 + -3 -1b = 7 + -3 Combine like terms: 7 + -3 = 4 -1b = 4 Divide each side by '-1'. b = -4 Simplifying b = -4
| -6(-1)+2= | | (8)(15)(5)(9)= | | 12.99x=30 | | 6-3x=4x+9 | | a-15=-19 | | (1/3x)-(2/4x)=(3/4) | | 5x^3=130 | | 3(2x-2)=10+x | | (4x-12)+52=90 | | -6(0)+2= | | 3(4x+5)-5(7x-7)=2(6x+1) | | 0=x^2-9x-8 | | -(x+11)=2(2x-6) | | 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t |